USE OF PROFESSIONAL MANAGEMENT COMPANIES IN MANAGEMENT OF HOUSING FUND (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Housing is the largest sector of public utilities, which includes the management of the housing stock, enterprises (companies) that provide services to the housing stock, and facilities that serve the population.It should be noted that any dwelling is considered property, regardless of the form of ownership.Property management is any relationship between property owners in relation to one or more property objects in order to achieve their goals.Therefore, the landlord is directly involved in the management of the housing stock by the landlord, management organizations and service providers. The objects of the land within the forms of property have a special place due to their social significance. Because a person spends most of his life at home. Therefore, special attention is paid to the condition of the housing stock, the quality of public utilities and life safety.